Therapy Okupasi dan Kognitif Lansia - I Wayan Suardana (Jurnal Gema Keperawatan, 2016)
This study aims to determine the relationship of occupational therapy with cognitive status in the elderly. This study was designed as retrospective study a comparative studied that conducted on a sample of 60 people are selected for each by simple random sampling. From the analysis found there was relationship between occupational therapy with cognitive state of elderly with Chi-Square scores was 34.2 and p = 0.00 (P 0.05) and OR of 55 at α 0.05 CI: (11141-271509). Which means that elderly people who do not to do occupational therapy 55 times more likely to experience cognitive decline compared to the elderly given occupational therapy.